Investigation and experiment of radar systems in unmanned aerial vehicles - I - Chua, Wei Xiang (2014)
With the rapid improvement of technologies, many organisations have been upgrading themselves to keep up with the advancements of technologies. This applies to the military world as well. Some key aspects of the current military technology are the usage of Synthetic Aperture Radar (SAR) and Unmanned Aerial Vehicle (UAV). SAR is used to capture high resolution images as well as moving target detection under various weather conditions.